PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, DAN MOTIVASI TERHADAP SEMANGAT KERJA PADA KARYAWAN BAGIAN PRODUKSI DI PT WIRA KARYA PRAMITRA TAPUNG KABUPATEN KAMPAR - Juliana Sari, Juliana Sari; Marzolina, Marzolina; Rendra, Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine and analyze the influence of leadership, work environment and motivation simultaneously on work enthusiasm of Production Department employees at PT Wira Karya Pramitra. The populations were 55 employees of PT Wira Karya Pramitra's production department and used a saturated sample. The data used in this study were primary data and secondary data. Technique collecting the data was questionnaires and documentation. The analysis tool used in this study was multiple linear regression analysis with work enthusiasm as dependent variable and three independent variables are leadership, work environment and motivation. The results of this study stated that leadership, work environment and motivation have significant effect on the work enthusiasm.Keyword: Leadership, Work Environment, Motivation, Work Enthusiasm